JASA TRANSPORTASI UDARA INDONESIA - siagian, wilson (Jurnal Sosial Humaniora, 2011)
All flight passengers want to be faster arrive in their destination and comfortable and safe as well. By arrive earlier it means the fare could be efficient and save some valuable time. Air transportation service becomes an alternative choice which is more favorable than land and water transportation. However, since the fare is significant high (under year 2000 period of time), the passengers have to postpone their desire to use the flight. After year 2000 (2000-2010) air fare or ticket fare has been adjusted with consumer demand and becomes very cheap. Therefore, everybody relatively could afford the fare ever since. However, there is a big question regarding the price of the ticket and its relation to the organization sustainable. Expertise wonder could the short term and especially long term operational cost of the company could be covered by the ticket fare alone in long term? There are some flight companies that withdrawn or back off from this business. Some of their planes are not able to fly technically and could not pass the requirement of fly permission from the Government which is conducted as a surveyor of national flight services. This study aims to identify such impact; is there more flight companies back off from the business and what the reason behind such decision